2009
DOI: 10.1016/j.ydbio.2008.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Why the embryo still matters: CSF and the neuroepithelium as interdependent regulators of embryonic brain growth, morphogenesis and histiogenesis

Abstract: The key focus of this review is that both the neuroepithelium and embryonic cerebrospinal fluid (CSF) work in an integrated way to promote embryonic brain growth, morphogenesis and histiogenesis. The CSF generates pressure and also contains many biologically powerful trophic factors; both play key roles in early brain development. Accumulation of fluid via an osmotic gradient creates pressure that promotes rapid expansion of the early brain in a developmental regulated way, since the rates of growth differ bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 69 publications
2
89
0
5
Order By: Relevance
“…Many such signals have been found in fetal CSF (fCSF), indicating that fCSF is part of the neurogenic niche (Owen-Lynch et al, 2003;Gato et al, 2005;Miyan et al, 2006;Johanson et al, 2008Johanson et al, , 2011Gato and Desmond, 2009). Two proteomic analyses of fetal CSF of rats and humans have revealed numerous compounds that likely are cues for diff erent phases of neurogenesis (Parada et al, 2005;Zappaterra et al, 2007).…”
Section: Alterations Of the Microenvironment Of The Neu-rogenic Nichementioning
confidence: 99%
“…Many such signals have been found in fetal CSF (fCSF), indicating that fCSF is part of the neurogenic niche (Owen-Lynch et al, 2003;Gato et al, 2005;Miyan et al, 2006;Johanson et al, 2008Johanson et al, , 2011Gato and Desmond, 2009). Two proteomic analyses of fetal CSF of rats and humans have revealed numerous compounds that likely are cues for diff erent phases of neurogenesis (Parada et al, 2005;Zappaterra et al, 2007).…”
Section: Alterations Of the Microenvironment Of The Neu-rogenic Nichementioning
confidence: 99%
“…For example, it has been suggested that FGF2 may act on neurogenesis by driving cells to terminal mitoses (Martin et al, 2006), and that the action of lipoproteins in this cellular process is the supply to the neuroepithelial cells of the necessary building materials (Parada et al, 2008b). Moreover, the presence of other neurogenic factors in the E-CSF has been suggested to account for overall neurogenesis (Martin et al, 2006;Parada at al., 2008a;Gato and Desmond, 2009). Our results show that mesencephalic neurogenesis in chick embryos is also driven by RA activity, which comes from the IsO, which in turn is regulated by E-CSF via the RBP and the all-trans retinol it contains.…”
Section: Ra Is Involved In Neurogenesis Induced By E-csfmentioning
confidence: 99%
“…Recently, it has been shown that E-CSF plays an important role in brain development at both embryonic and foetal stages and performs several crucial functions (reviewed by Gato and Desmond, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As cerebrospinal fluid (CSF) contains a variety of signaling factors (Parada et al, 2008, Gato andDesmond, 2009;Huang et al, 2010;Johansson et al, 2010;Lehtinen et al, 2011) its composition might contribute to the unique niche environment of the neural stem cells lining the ventricle .…”
Section: Introductionmentioning
confidence: 99%